2017
DOI: 10.1080/23744235.2017.1358461
|View full text |Cite
|
Sign up to set email alerts
|

Haematuria is a marker for the severity of acute kidney injury but does not associate with thrombocytopenia in acute Puumala hantavirus infection

Abstract: Combined positive result of haematuria and proteinuria in the dipstick test at hospital admission predicted the severity of upcoming AKI in acute PUUV infection. As haematuria was not associated with the severity of thrombocytopenia, it did not indicate increased bleeding tendency, but was rather a marker of acute kidney injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…We have previously shown that albuminuria and hematuria in dipstick urine test predict the severity of upcoming AKI in patients with acute PUUV infection 7, 8. We now report that glucosuria in these patients is an even stronger predictor of disease severity.…”
mentioning
confidence: 53%
“…We have previously shown that albuminuria and hematuria in dipstick urine test predict the severity of upcoming AKI in patients with acute PUUV infection 7, 8. We now report that glucosuria in these patients is an even stronger predictor of disease severity.…”
mentioning
confidence: 53%
“…In PUUV infection, the flash-like appearance of albuminuria and the association between albuminuria quantity with upcoming AKI severity [6,11] are unique findings in the context of AKI. In addition, the amount of hematuria associates with the severity of AKI in PUUV infection [35].…”
Section: Discussionmentioning
confidence: 99%
“…In PUUV infection, the flash-like appearance of albuminuria and the association between albuminuria quantity with upcoming AKI severity [ 6 , 11 ] are unique findings in the context of AKI. In addition, the amount of hematuria associates with the severity of AKI in PUUV infection [ 35 ]. The presence of glucosuria, detected in 12% of the patients, was a strong predictive factor not only for clinical shock, but also the severity of AKI in acute PUUV infection [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found a prevalence of 50% hematuria at admission, whereas other studies have reported prevalences of 25%–58% ( 11 , 23 , 27 ). At least 1 study found an association between hematuria (but not thrombocytopenia) and progression to severe AKI ( 28 ). Hematuria is also considered a marker of NE severity predictive of polyuria ( 29 ).…”
Section: Discussionmentioning
confidence: 99%